2007
DOI: 10.1245/s10434-006-9255-x
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal and Truncal Sarcomas: Prognosis Depends Upon Type Not Location

Abstract: Successful operative resection can confer prolonged disease-free survival and cure for truncal and retroperitoneal sarcomas. Histological subtype, not location, is predictive of long-term survival. Future studies should focus on histological subtype rather than tumor location for truncal and retroperitoneal sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 26 publications
3
56
1
3
Order By: Relevance
“…Certain previous studies support the above argument and indicate that if the liposarcoma invaded the kidney, then combined resection of the kidney is necessary (9,25). There is no evidence that chemotherapy or radiotherapy improve survival rates (26). In the present study, no patients in the studied literature were administered chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 55%
“…Certain previous studies support the above argument and indicate that if the liposarcoma invaded the kidney, then combined resection of the kidney is necessary (9,25). There is no evidence that chemotherapy or radiotherapy improve survival rates (26). In the present study, no patients in the studied literature were administered chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 55%
“…However, because these studies were done in select patients at specialized centers, it is still uncertain how the introduction of imatinib has impacted survival on a broader level within the U.S. population. Previous population-based data have suggested an improvement in survival after 2000 in patients with gastrointestinal mesenchymal neoplasms (35). However, this study was done using a heterogeneous sample population with various stages of disease and a variety of histologies other than gastrointestinal stromal tumor, including other gastrointestinal smooth muscle tumors and nerve sheath tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In the report by Perez et al, a recent meta-analysis of the pertinent literature regarding retroperitoneal soft tissue sarcomas failed to show significant radiotherapy-related survival benefits in the treatment retroperitoneal liposarcoma [9] . Matsushita et al reported that chemotherapeutic agents such as doxycycline and ifosfamide demonstrating activity against metastatic sarcoma, but such chemotherapeutic agents have not shown survival benefit [5] .…”
Section: Discmentioning
confidence: 99%